The spoken word: Oral culture in Britain, 1500-1850 - Woolf, Daniel (Manchester University Press, 2003)
The early modern period was of great significance throughout Europe with respect to its gradual transition from a largely oral to a fundamentally literate society. On the one hand, the spoken word remained of the utmost importance to the dissemination of ideas, the communication of information and the transmission of the cultural repertoire. On the other hand, the proliferation of written documents of all kinds, the development of printing and the spread of popular literacy combined to transform the nature of communication. Studies previous to this have traditionally focussed on individual countries or regions, and emphasised the contradictions between oral and literate culture. The essays in this fascinating collection depart from these approaches in several ways. By examining not only English, but also Scottish and Welsh oral culture, they provide the first pan-British study of the subject. The authors also emphasise the ways in which oral and literate culture continued to compliment and inform each other, rather than focusing exclusively on their incompatibility, or on the 'inevitable' triumph of the written word. The chronological focus, ranging from the sixteenth to the mid-nineteenth century, with glances ahead to the twentieth, set the problem against a longer chronological span than most other studies, providing a link between early modern and modern oral and literate cultures. This book it will be of interest to students and scholars of British history, Linguistics, Literary Studies and Folklore Studies.